Advances and challenges in genetic engineering of microalgae. (2nd January 2019) - Fajardo, Carlos; De Donato, Marcos; Carrasco, Rafael; Martínez‐Rodríguez, Gonzalo; Mancera, Juan Miguel; Fernández‐Acero, Francisco Javier
Abstract: Knowledge at the molecular level of microalgae has obtained great scientific interest in recent years, because of their potential for biofuel production, as well as other highly valued molecules. Recent advances in the area of the genetic manipulation of microalgae open an entirely new field of possible applications for these organisms as biorefineries. This review represents a compendium that gathers the main milestones that have marked the area of genetic engineering in microalgae during the last decade, from classical techniques for the transformation and expression of transgenes, to the most avant‐garde techniques currently used for gene silencing and DNA edition, as well as a discussion about the future perspectives in this field.